Mitochondria–lysosome contacts regulate mitochondrial fission via RAB7 GTP hydrolysis - Wong, Yvette C.; Ysselstein, Daniel; Krainc, Dimitri (Nature (London), 2018)
Formation of inter-organelle contacts between mitochondria and lysosomes, regulated by lysosomal RAB7 GTP hydrolysis, allows for bidirectional regulation of mitochondrial and lysosomal dynamics. Contacts inside cell walls Cellular organelles such as mitochondria and lysosomes are dynamic entities that communicate with each other not just through vesicular trafficking but also by direct, albeit transient, contact between different organelles. Dimitri Krainc and colleagues report the existence of inter-organelle contacts between mitochondria and lysosomes—a phenomenon that seems to be independent of the association between damaged mitochondria and lysosomes in the context of the degradative process of mitophagy. The authors also identify organelle-specific molecules that mediate the tethering between these two organelles and demonstrate that lysosome–mitochondrion contacts allow bidirectional regulation of the dynamics of these organelles. Both mitochondria and lysosomes are essential for maintaining cellular homeostasis, and dysfunction of both organelles has been observed in multiple diseases 1 , 2 , 3 , 4 . Mitochondria are highly dynamic and undergo fission and fusion to maintain a functional mitochondrial network, which drives cellular metabolism 5 . Lysosomes similarly undergo constant dynamic regulation by the RAB7 GTPase 1 , which cycles from an active GTP-bound state into an inactive GDP-bound state upon GTP hydrolysis. Here we have identified the formation and regulation of mitochondria–lysosome membrane contact sites using electron microscopy, structured illumination microscopy and high spatial and temporal resolution confocal live cell imaging. Mitochondria–lysosome contacts formed dynamically in healthy untreated cells and were distinct from damaged mitochondria that were targeted into lysosomes for degradation 6 , 7 . Contact formation was promoted by active GTP-bound lysosomal RAB7, and contact untethering was mediated by recruitment of the RAB7 GTPase-activating protein TBC1D15 to mitochondria by FIS1 to drive RAB7 GTP hydrolysis and thereby release contacts. Functionally, lysosomal contacts mark sites of mitochondrial fission, allowing regulation of mitochondrial networks by lysosomes, whereas conversely, mitochondrial contacts regulate lysosomal RAB7 hydrolysis via TBC1D15. Mitochondria–lysosome contacts thus allow bidirectional regulation of mitochondrial and lysosomal dynamics, and may explain the dysfunction observed in both organelles in various human diseases.